DAMPAK KRISIS EKONOMI DAN MASUKNYA BANK UMUM PADA PASAR KREDIT USAHA MIKRO KECIL TERHADAP KINERJA BANK PERKREDITAN RAKYAT (BPR) DIY - Murti Lestari (KINERJA, 2014)
The economic crisis and the entry of commercial banks in the small micro-credit market is estimated to have an impact on rural banks (BPR) business. By using time series data, and using performance measures such as the performance of rural banks lending, third-party funds (savings and deposits), lending rates, and spreads, the study concluded that the entry of commercial banks in the small micro-credit markets do not interfere (negative affect) the performance of BPR DIY. In terms ofthe economic crisis, the response performance of BPR DIY show mixed reactions. In terms of lending and third-party funds, the economic crisis actually makes BPRis able to raise his credit and increase the ability to collect deposits. While in the case of the determination of interest rates, the crisis negatively affect the interest rate (lower lending rates). Similarly, for a variable spread, the crisis also have negative impacts, which means that with the economic crisis, the ability of BPR take spread decreases.Keywords: rural bank, micro and small enterprises credit, crisis economy